2015
DOI: 10.1007/s10661-015-4915-6
|View full text |Cite
|
Sign up to set email alerts
|

Groundwater vulnerability assessment in agricultural areas using a modified DRASTIC model

Abstract: Groundwater contamination is a major concern for groundwater resource managers worldwide. We evaluated groundwater pollution potential by producing a vulnerability map of an aquifer using a modified Depth to water, Net recharge, Aquifer media, Soil media, Topography, Impact of vadose zone, and Hydraulic conductivity (DRASTIC) model within a Geographic Information System (GIS) environment. The proposed modification which incorporated the use of statistical techniques optimizes the rating function of the DRASTIC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 36 publications
1
19
0
1
Order By: Relevance
“…chloride [Cl]) in different hydrogeologic settings to further explore their potential to establish reliable groundwater vulnerability maps. Previously, Sadat‐Noori and Ebrahimi () employed the Wilcoxon test for the modification of the DRASTIC framework in the Saveh‐Nobaran plain aquifer in Iran, using Cl concentrations. This study showed that the R 2 between the Cl concentration data and the modified vulnerability index increased significantly, from 0.52 to 0.78.…”
Section: Resultsmentioning
confidence: 99%
“…chloride [Cl]) in different hydrogeologic settings to further explore their potential to establish reliable groundwater vulnerability maps. Previously, Sadat‐Noori and Ebrahimi () employed the Wilcoxon test for the modification of the DRASTIC framework in the Saveh‐Nobaran plain aquifer in Iran, using Cl concentrations. This study showed that the R 2 between the Cl concentration data and the modified vulnerability index increased significantly, from 0.52 to 0.78.…”
Section: Resultsmentioning
confidence: 99%
“…Transmissivity was obtained from the pumping tests. This approach has been applied in different studies (Saidi et al 2010;Sadat-Noori and Ebrahimi 2015).…”
Section: Structure Of Each Model For Evaluating Drastic Indicesmentioning
confidence: 99%
“…The vulnerability indices have been correlated with nitrate concentrations and/or controlled with sensitivity analysis in most of the previous studies (Rupert 2001;Huan et al 2012;Neshat et al 2014a;Pacheco et al 2014;Ahmed et al 2015;Vaezihir and Tabarmayeh 2015). Recent researchers made alteration to rating scales to adjust the model by data interpolation (kriging method) using ArcGIS® (Ahmed et al 2015;Vaezihir and Tabarmayeh 2015;Sadat-Noori and Ebrahimi 2015). In addition, modifying the model with omitting or adding layers such as land use pattern to estimate contamination risk to pollutants mostly nitrate (Panagopoulos et al 2006;Bai et al 2012;Huan et al 2012;Neshat et al 2014a;Ahmed et al 2015;Kazakis and Voudouris 2015;Vaezihir and Tabarmayeh 2015) or applying analytic hierarchy process (AHP), a multiple criteria decision-making (MCDM) technique, to adjust weights of the DRASTIC parameters to local settings have become prevalent (Sener and Davraz 2013;Neshat and Pradhan 2014;Neshat et al 2014a).…”
Section: Introductionmentioning
confidence: 99%
“…However, reliable quantitative determination of groundwater pollution risk is difficult as it depends on many factors, some of the mhardly measurable, and thus assessments of groundwater pollution risk are usually qualitative instead quantitative. Some groundwater pollution risk assessments focus on the risk stemming from only one specific source of pollution, for example nitrates derived from agricultural fertilization [11][12][13][14][15][16][17][18][19], waste disposal sites [20,21], or even biofuel-related land use [22].…”
mentioning
confidence: 99%
“…Locally measured nitrate concentrations are usually taken as an indicator of current degradation of groundwater quality, such as in [11][12][13][14][15][16][17][18][19]. In this way, a purely theoretical possibility of occurrence of an unwanted event is linked with real facts.…”
mentioning
confidence: 99%